An Ancient Egyptian Rudder from Thonis-Heracleion. (3rd July 2022) - Belov, Alexander
ABSTRACT: The city of Thonis-Heracleion, a major ancient port on the Mediterranean coast of Egypt in the Late and Ptolemaic Periods, contains the largest known accumulation of ancient ships in the world. During the last excavation season in the spring of 2021, a small rudder was discovered in the vicinity of one of the shipwrecks. The article is devoted to the context and construction of the rudder.